Mongrels or marvels : the Levantine writings of Jacqueline Shohet Kahanoff - Kahanof, Jacqueline (Stanford studies in Jewish history and culture., 2011)
The writings of Jacqueline Shohet Kahanoff (1917-1979) offer a refreshing reassessment of Arab-Jewish relations in the Middle East. This text embraces the idea of a pluralist, multicultural society and counters the prevailing attitudes and identity politics in the Middle East with the possibility of mutual respect and acceptance.